Artists in residence - United Nations Educational, Scientific; Cultural Organization; Florencia Abbate (The UNESCO Courier, 2023)
By opening the doors to her house, Victoria Ocampo aimed to stimulate a fertile dialogue between the intellectuals and artists of her time. García Lorca and Stravinsky, among many others, stayed there for a few days or even several months. A tireless patron of the arts, she didn’t hesitate to sacrifice a few of her personal possessions to give life to her project, built around friendship.